(untitled) (Tanzania Medical Journal, 2015)
Background: Thromboembolic and bleeding complications are the main causes of morbidity and mortality in patients with mechanical heart valves1. The risk factors for these complications in Tanzania have not been established. Methods: A retrospective cohort study was conducted among patients with mechanical heart valves operated from 1990 to 2003 attending the Muhimbili National Hospital. Information on occurrence and risk factors for thromboembolic and bleeding complications was obtained from medical records and interview. Findings: Among the 232 study patients, 59(25.4%) suffered a total of 83 thromboembolic episodes. In a multivariate Cox regression analysis, residing very far away from only anticoagulation in Dar es Salaam and mitral valve replacement were found to be predictors of thromboembolism. In a univariate (not multivariate) logistic regression analysis, increased left ventricular diameters, mean aortic valves pressure gradient and reduced ejection fraction were significantly associated with thromboembolism. The study also indicated that 87 (37.5%) patients suffered a total of 132 bleeding events.. In the multivariate Cox regression of potential risk factors, those patients who attended both cardiac and anticoagulation clinic had less episodes of bleeding complications compared to those who had attended cardiac clinic only. Patients who had no history of /coexisting bleeding disorder at baseline were found to have a reduced risk of bleeding complications compared to those who had. Conclusions: The cause of thromboembolic and bleeding complications was multifactor in nature and management should be focused in identifying these multiple factors.